An Analysis on the Use of Google AdWords to Increase E-Commerce Sales - Za, Saida Zainurossalamia; Tricahyadinata, Irsan (International Journal of Social Sciences and Management, 2017)
The development of information and communication technology affected many aspects of life, including economical state. E-commerce is an activity of selling or buying goods and services through the internet by using electronic media. The optimization of e-commerce could be carried out by advertising. Google AdWords is one of online advertising technologies that provides benefits in the business of e-commerce. This research was aimed to analyze and describe the improvement of the e-commerce sales by using Google AdWords. The research design was qualitative research design by utilizing secondary data from Google, Inc. Based on the result of the research, the e-commerce sites received increasing visits to the websites, increasing numbers of the new customers, increasing sales, and even business expansion. It could be concluded that Google AdWords was highly useful to enhance e-commerce. The researcher suggested to utilize Google AdWords online-advertising system in the e-commerce activities. Future researchers are suggested to use the revealed data as the basis of further research in relevant field. Int. J. Soc. Sc. Manage. Vol. 4, Issue-1: 60-67